1995
DOI: 10.1016/0168-6496(94)00068-8
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal transfer at natural population densities in a microcosm simulating an estuarine environment

Abstract: Estuarine microcosmswere used to follow conjugal transfer of a broad host range IncPl plasmid from a Pseudomonas putidu donor to indigenous bacteria. Donor cells were added at a concentration similar to the natural abundance of bacteria in the water column (lo6 cells ml-'). Transfer was not detected in any of the test microcosms (calculated limit of detection of lo-' and 10m4 transconjugants donor-' in water column and sediment, respectively), with the exception of transfer to an isogenic recipient (added at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The development of resistance to antimicrobial agents by many bacterial pathogens has compromised traditional therapeutic regimens, making treatment of infections more difficult [4]. Three factors have contributed to the development and spread of resistance: mutation in common genes that extend their spectrum of resistance, transfer of resistance genes among diverse microorganisms, and increase in selective pressures that enhance the development of resistant organisms [4,[20][21][22][23][24].…”
Section: Effects Of Hospital Wastewater On Aquatic Ecosystemsmentioning
confidence: 99%
“…The development of resistance to antimicrobial agents by many bacterial pathogens has compromised traditional therapeutic regimens, making treatment of infections more difficult [4]. Three factors have contributed to the development and spread of resistance: mutation in common genes that extend their spectrum of resistance, transfer of resistance genes among diverse microorganisms, and increase in selective pressures that enhance the development of resistant organisms [4,[20][21][22][23][24].…”
Section: Effects Of Hospital Wastewater On Aquatic Ecosystemsmentioning
confidence: 99%
“…Habitats investigated in this way (Table 1) include river water and epilithon [13, 14, 19–21], lake water [16, 17, 22], marine water and sediment [23–33], estuarine water and sediment [34], drinking water [35] and wastewater [36, 37]. A typical example is the beaker microcosm used by Bale et al [13–15] and Hill et al [20] to investigate gene transfer in river epilithon.…”
Section: ‘Simple’ Microcosmsmentioning
confidence: 99%
“…Gene transfer by conjugation has been shown to occur in a wide variety of laboratory systems simulating diverse environmental habitats such as soil [3^7], sea water [8,9], freshwater [10], sediments [8,11], bio¢lms [12] and sludge [13]. However, our own studies have shown infrequent spread of a plasmid by conjugation, when natural population densities were employed, in microcosms simulating the water column and bulk sediment of an aquatic ecosystem [8]. Hence, we hypothesized that in aquatic environments, conjugal gene transfer is localized to habitats de¢ned by high bacterial densities and availability of growth substrates.…”
Section: Introductionmentioning
confidence: 99%